A brief introduction to the philosophy of information (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2017)
The term “information” and its various meanings across several domains have spawned a growing research area in the discipline of philosophy known as the philosophy of information (PI). The following briefly outlines a taxonomy of the field addressing: 1) what is the philosophy of information; 2) what is information; 3) open problems in the philosophy of information; 4) paradoxes of information; 5) philosophy as the philosophy of information; 6) information metaphysics; and 7) information ethics.Keywords: Philosophy of information. Information.Link: http://revista.ibict.br/fiinf/article/view/3005/2755